Contributions of SGK3 to transporter-related diseases - Liao, Qian-Qian; Dong, Qing-Qing; Zhang, Hui; Shu, Hua-Pan; Tu, Yu-Chi; Yao, Li-Jun (Frontiers in Cell and Developmental Biology, 2022)
Serum- and glucocorticoid-induced kinase 3 (SGK3), that is ubiquitously expressed in mammals, is regulated by estrogens and androgens. SGK3 is activated by insulin and growth factors through signaling pathways involving phosphatidylinositol 3-kinase (PI3K), 3-phosphoinositide-dependent kinase 1 (PDK-1) and mammalian target of rapamycin complex 2 (mTORC2). Activated SGK3 can activate ion channels (TRPV5/6, SOC, Kv1.3, Kv1.5, Kv7.1, BKCa, Kir2.1, Kir2.2, ENaC, Nav1.5, ClC-2, ClC Ka), carriers and receptors (Npt2a, Npt2b, NHE3, GluR1, GluR6, SN1, EAAT1, EAAT2, EAAT4, EAAT5, SGLT1, SLC1A5, SLC6A19, SLC6A8, NaDC1) and Na+/K+-ATPase, promoting the transportatin of calcium, phosphorus, sodium, glucose and neutral amino acids in the kidney and intestine, promoting the absorption of potassium and neutral amino acid in the renal tubules, promoting the transport of glutamate and glutamine in the nervous system, and promoting the transportatin of creatine. SGK3 sensitive transporters contribute to a variety of physiological and pathophysiological processes, such as maintaining calcium and phosphorus homeostasis, hydro-salinity balance and acid-base balance, cell proliferation, muscle action potential, cardiac and neural electrophysiological disturbances, bone density, intestinal nutrition absorption, immune function and multiple substance metabolism.These processes are related to kidney stones, hypophosphorous rickets,multiple syndromes, arrhythmia, hypertension, heart failure, epilepsy, Alzheimer's disease，amyotrophic lateral sclerosis , glaucoma , ataxia Idiopathic deafness and other diseases.